Acute murine cytomegalovirus infection boosts cell-type specific response and lipid metabolism changes in the liver of infant mice - Gao, Juanzi; Wang, Anmin; Bu, Xiangyi; Jia, Weidong (Frontiers in Immunology, 2023)
In infants, human cytomegalovirus (HCMV) infection can cause severe diseases, including neonatal hepatitis; however, the single-cell dimensional mechanism of immune cell alteration after contracting the first CMV infection is still unknown.Hepatocytes play an essential role in metabolic homeostasis and detoxification; however, the effects of CMV infection on hepatic lipid metabolism in infants are still unclear. Based on single-cell RNA-sequencing, we found that murine MCV (MCMV) infected most liver cell types in infant mice and increased the percentage of proliferating CD8 effector T cells and a subset of Nos2 + monocytes; these cells may vital in the early anti-viral process. Furthermore, MCMV infection altered the protein expression profile of lipid metabolism in hepatocytes.Knocking down the key transcription factor PPAR-γ in hepatocytes inhibited CMV infection. Overall, our data highlighted the immune system response to early-stage MCMV infection and the impact of infection on hepatic lipid metabolism in infant mice.